2013
DOI: 10.4067/s0034-98872013000900002
|View full text |Cite
|
Sign up to set email alerts
|

Nivel sérico de folato y vitamina B12 en adultos mayores chilenos: Resultados de la Encuesta Nacional de Salud ENS 2009-2010

Abstract: Background: Supraphysiological levels (SFL) of serum folate (SF) derived from flour fortification with folic acid (FA) could be risky among older adults with low 41-20 (normal) and 21.2 ± 0.56/38.6 µg/L and 348.4 ± 7.6/637(pg/ml) (Rev Med Chile 2013; 141: 1107-1116.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Our study on subjectively healthy elderly Caucasian participants from a circumscribed geographical region shows for the first time that holoTC, but also vitamin B12 levels from 60 year onwards remain within RIs set by international expert panels with people from all ages [ 42 , 43 ] whereas serum folate concentrations – though not RBC folate - recede to some extent. It could be shown that MMA, Hcy as well as Fedosov’s wellness quotient rather are associated with kidney function than with age.…”
Section: Discussionmentioning
confidence: 66%
“…Our study on subjectively healthy elderly Caucasian participants from a circumscribed geographical region shows for the first time that holoTC, but also vitamin B12 levels from 60 year onwards remain within RIs set by international expert panels with people from all ages [ 42 , 43 ] whereas serum folate concentrations – though not RBC folate - recede to some extent. It could be shown that MMA, Hcy as well as Fedosov’s wellness quotient rather are associated with kidney function than with age.…”
Section: Discussionmentioning
confidence: 66%
“…24 Population studies of adults aged 65 years or older without HF in the same country have shown the following prevalence of B12 deficiency (with WHO cut-off points): Sánchez et al 27 report 12% in a sample of 1028 subjects, increasing to 25.4% when marginal deficiency is included; Cabrera et al 28 report 11.3% in a similar sample of 1013 subjects; and Castillo-Lancellotti et al report 8.1% in a sample of 1043 subjects. 29 The results of this study show higher prevalence levels than these. In addition, the fact that there are no differences in deficiency at different age ranges suggests that it may be useful to consider older adults with HF as a specific risk group for vitamin B12 deficiency, like other risk factors that have previously been described: rurality, 20 pernicious anaemia, gastrectomy, veganism, and metformin consumption.…”
Section: Discussionmentioning
confidence: 42%
“…Results from the 2009-2010 Chilean National Health Survey showed that 49% of people aged ≥65 years (n = 1043) had high levels of serum folate (>29 µg/L [80th percentile of the distribution]). 27 As a result of these concerns, the Ministry of Health convened a meeting in 2008 with representatives from industry, the National Public Health Institute, and INTA to address the issue of a potential excessive intake of folate in some segments of the population. Several modifications were suggested and approved, which included lowering the range of fortification of folic acid from 2.0 to 2.4 mg/kg to 1.8 to 2.0 mg/kg and increasing the concentrations of riboflavin and niacin.…”
Section: Flour Fortification Of Wheat Flour and Ntds In Chilementioning
confidence: 99%
“…Results from the 2009-2010 Chilean National Health Survey showed that 49% of people aged 65 years (n ¼ 1043) had high levels of serum folate (>29 mg/L [80th percentile of the distribution]). 27 As Industry buy-in and willing participation was essential in all cases. Sugar had never been fortified anywhere in the world before Arroyave tried in Guatemala.…”
Section: Recent Developmentsmentioning
confidence: 99%